Sonolytic degradation of bisphenol S: Effect of dissolved oxygen and peroxydisulfate, oxidation products and acute toxicity. (15th November 2019) - Lu, Xiaohui; Zhao, Jingnan; Wang, Qun; Wang, Da; Xu, Haodan; Ma, Jun; Qiu, Wei; Hu, Tao
Abstract: In this paper, the kinetics of bisphenol S (BPS) degradation in the presence of peroxydisulfate (PDS) or dissolved oxygen (DO) in ultrasound (US) system were investigated. For PDS (US/PDS), increased PDS concentration result in faster BPS degradation, but the enhancement was not remarkable with multiplying PDS dosages. Therefore, heterogeneous PDS activation model based on a Langmuir-type adsorption mechanism was proposed to explain the trait of BPS abatement. The equilibrium constant of PDS (KPDS ) was calculated to be 2.91 × 10 −4 /μM, which was much lower than that of BPS, suggesting that PDS was hard to adsorb on the gas-liquid interface of the cavitation bubble following by activation. Besides, the formation of OH and SO4 − in US/PDS system was reinvestigated. The result showed that SO4 − rather than OH was the predominant radical, which was quite different from previous study. Dissolved oxygen largely improve the degradation of BPS in US system and OH rather than O2 − was proved to be the main reactive oxygen species (ROS). The improvement of OH generation possibly caused by the reaction of DO with H so that it cannot recombine with OH. The transformation of the BPS in US system mainly included BPS radical polymerization, hydroxylation and hydrolysis. Frustratingly, the acute toxicity assay of Vibrio fischeri suggests that the degradation products of BPS are more toxic. These results will improve the understanding on the activation mechanisms of PDS and the role of dissolved oxygen play in US. Further investigations may need to explore other treatment ways of BPS and evaluate the acute toxicity of degradation products. Graphical abstract: Image 1 Highlights: SO4 . − rather than OH was the predominant radical in US/PDS system. Heterogeneous PDS activation model was proposed and applied to simulate the BPS degradation. The generation and formation routes of superoxide radical ion (O2 . - ) were verified. .OH was proved as the main reactive oxidative species (ROS) in the presence of DO in US system. Degradation products of BPS in the US/PDS system were identified and the post-treatment toxicity of BPS was evaluated.